Slow solar wind acceleration through the middle corona: Spacecraft radio studies - Wexler, David B.; Kooi, Jason E.; Jensen, Elizabeth A.; Song, Paul (Frontiers in Astronomy and Space Sciences, 2022)
The "Middle Corona'', defined by recent consensus as the region spanning 1.5-6 solar radii (R$_\odot$, heliocentric), is an important zone through which several structural and dynamic changes occur in coronal streamer regions. Among these is a regime change from high density, closed magnetic field structures to open field structures of much lower electron concentration. Along with this complex restructuring, the forming slow solar wind is channeled and accelerated through the middle corona. Solar wind (SW) outflow speeds can be estimated from trans-coronal radio observations. The method of radio frequency fluctuation (FF) analysis considers the frequency variations arising from density inhomogeneities crossing the sensing line-of-sight (LOS). Below 2 R$_\odot$, where the SW is beginning to form and outflow speed is expected to be below the acoustic wave speed, the radio FF can be attributed to the density oscillations of acoustic waves crossing the radio sensing path. With increasing helioaltitudes through the middle corona, the FF are dominated by density disturbances advected across the sensing LOS. This property enables estimation of solar wind outflow speed at various heliodistances. The coronal plasma is believed to enter the middle corona in a subsonic state, then accelerate to exit the zone generally with supersonic, but sub-Alfv\'enic flows. Trans-coronal radio sensing complements imaging and other remote coronal observations, and helps bridge the observational gap across the full distance range of the middle corona. Radio techniques enrich the study of solar wind, and should be utilized in next-generation, multiwavelength campaigns that tackle coronal plasma acceleration.